A Preformulation of a Water Soluble Furosemide Dosage Form - Syukri, Yandi; Yuwono, Tedjo; Hakim, Lukman (Indonesian Journal of Pharmacy, 2002)
Solid dispersion system of water-insoluble furosemide in polyvinylpirolidon (PVP) was prepared by a solvent method in various ratios of 1 : 1, 1 : 3, 1 : 5, 1 : 7 and 1 : 9 of the drug and PVP, respectively in order to improve furosemide solubility and dissolution. The improvement of furosemide solubility was studied by a solubility method in a shaking waterbath. The solubility test showed that various concentrations of PVP and temperature gave statistically significant increased of furosemida solubility (P < 0,05). The dissolution study of furosemide solid dispersion system was done using a dissolution tester at the rotation rate of 50 rpm. Furosemide concentration released was determined spectrophotometrically using a UV spectrofometer. This test showed a significant increased of furosemida solubility (P < 0,05), but with a prolonged of releasing time.Key Word : solid dispersion, solubility, dissolution, bioavailability.